Kontinuität oder Bruch? Eliten als Akteure bei der Konzeptualisierung von Nation und Staat in der Slowakei von 1938 bis 1948 - Kolková, Stanislava; Justus Liebig University Giessen (My University, 2015)
Der Fokus dieser Arbeit liegt in der Untersuchung der Dynamik der slowakischen Wissenseliten und deren Rolle beim Transfer von politisch-gesellschaftlichen Konzepten in den slowakischen Kontext in einer der kontroversesten Perioden der slowakischen Geschichte der Autonomie und der Selbständigkeit von 1938 bis 1945 sowie der unmittelbaren Nachkriegszeit, d.h. von der Wiedereingliederung in die Tschechoslowakei im Jahr 1945 bis zum Februarumsturz im Jahr 1948. Vordergründig wird die Frage behandelt, welche Nations- und Staatskonzepte in der Slowakei von 1938 bis 1948 generiert und/oder übernommen wurden und ob und wie diese Konzepte in Kunst, Kultur und Wissenschaft rezipiert, reflektiert, transformiert, repräsentiert und medialisiert wurden. Einen wesentlichen Aspekt bildet die Frage, aus welchen Wissenskulturen diese Konzepte rezipiert wurden.Eliten verfügen in den gesellschaftlichen Systemen über Schlüsselfunktionen und sind für die soziale Stabilität verantwortlich. Besonders in politisch und wirtschaftlich unsicheren Zeiten wird von der Elite erwartet, als Stützen der Gesellschaft zu fungieren.Den Funktionseliten kam eine wesentliche Rolle nicht nur als Akteuren des Transfers zu, sondern auch bei der Herausbildung eines neuen Geschichtsbildes. Sie waren nicht nur für den Wissens- sondern auch für den Ideologietransfer bedeutend. Die Kunst arbeitet wesentliche Momente gesellschaftlicher Entwicklung mit besonderer Sensibilität heraus und zusammen mit den geisteswissenschaftlichen Fächern wie der Literaturgeschichtsschreibung oder Geschichte sollten sie einen nationalen Auftrag erfüllen. Deshalb ist es gerade in den geisteswissenschaftlichen Fächern sinnvoll, die Einflüsse und Wahrnehmung fremder Importe zu beobachten.Kulturelle und wissenschaftliche Eliten verfügen über massenwirksame Mechanismen d.h. kulturelle und wissenschaftliche Plattformen (fachspezifische Zeitschriften, Ausstellungen, Kongresse etc.), die der Verbreitung nationaler Geschichtskonzepte dienen bzw. dienen können und die sie für den Transfer nicht nur auf der nationalen bzw. regionalen Ebene, sondern auch für den Transfer kulturell-historischen Wissens in die Slowakei und den Transfer des Wissens über die Slowakei nutzten. Dabei sind innerhalb der Wissenseliten verschiedene Gruppierungen festzustellen, anhand deren sich die Textualisierung und Kontextualisierung der Nations- und Staatskonzepte und damit verbundene Diskurse nachverfolgen lassen.

The main focus of this work is to investigate dynamics of Slovak intellectual elites (Wissenseliten) and their role in the transfer and introduction of different socio-political concepts from foreign into the Slovak context during most controversial periods of Slovak history: 1) the autonomy and the "independence" (1938-1945), and 2) the immediate postwar period, from reintegration into Czechoslovakia in 1945 until the coup in February 1948. Some of the issues raised in this research are: What changes do the concepts of nation and state undergo during the given periods? Were these concepts generated from within Slovak contexts or imported? How were these concepts integrated and expressed in such mediums as art, culture and science? One of the most important questions to answer is: Which cultures of knowledge (Wissenskulturen) were these concepts borrowed from?It is obvious that the transformation of perception of concepts like "nation" and "state", their adaptation into the Slovak socio-political context was greatly influenced by the rapid radicalization of the European political landscape, especially since 1938. Moreover, Slovakia was on the intersection of variety of cultures of knowledge , interplay of which was no less predetermined by the state s geopolitical allegiances, like, for example, affiliation to larger geopolitical constructs (Austrian-Hungarian Monarchy, Czechoslovakia), or dependence on political superpowers in East Central Europe (Germany 1938-1945; Soviet Union since 1945).Thus it can be presumed that transnational cultural and scientific relations had impact not only on the transfer of knowledge from one context to another, but also on the reception of new ideas. The essential role in this exchange was played by national cultural and academic elites, who helped in reformulating, for example, the new conception of Slovakian history and who were instrumental not only for the transfer of knowledge, but also for the transfer of ideology. Therefore it is crucial to follow the evolution of Slovakian elites by asking questions like: What cultural contexts did they come from? What kind of interaction existed between different cultures of knowledge and what was the dynamics of interchange between them?The elites performed a vital social role by having a key-function in preserving social stability. According to KARL MANNHEIM, the intellectual and moral or religious elites have the task "to sublimate the spiritual energies". This means that science and culture, which are essential and indispensable for any modern society, must be further developed and unfolded. In parallel, the essential aspects of social development are most sensitively reflected in art, and together with other humanitarian disciplines, like history or literature, they should accomplish the "national mission". Therefore it makes sense, especially in the humanities, to observe and trace influences and perceptions of the imported "foreign ideas. Hence both groups of elites are responsible in the formulation of new concepts, because to do so one requires a specific and structured approach in the handling of knowledge.Finally, cultural and academic elites interact via publically accessible mechanisms which can be regarded as cultural and scientific platforms for exchange of ideas (specialist magazines, exhibitions, conferences, etc.). The platforms can be used for propagation of different concepts, like national history, and also used for wider transfer of knowledge not only on the national or regional levels, but also for transferring cultural-historical knowledge inside Slovakia and outside of the country. Thus, within the elites of knowledge one can establish a number of different groupings pertaining to textualization and contextualization of concepts like "nation" and "state" and related discourses.
Continuity or change? Elites as actors by the conceptualisation of nation and state in Slovakia from 1938 until 1948
Keywords: Eliten; Slowakei 1938-1948; nationale und staatliche Konzepte; Kontinuität; politischer Wandel; elites; Slovakia 1938-1948; continuity; concepts of nation and state; political change; ddc:900